VIRTUALISASI PEMBELAJARAN MENULIS DONGENG BERBASIS PRODUK ANYFLIP MELALUI SPADA KAMPUS MERDEKA - Ari Rohmawati; Anisa Fajriana Oktasari; Bambang Yulianto; Tengsoe Tjahjono; Syamsul Shodiq (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
Learning to write fairy tales boldly has limitations and challenges. Lecturers must organize creative and innovative learning to provide stimulus to students so they can take part in lectures optimally. The stimulus given with anyflip and the Merdeka Campus SPADA platform. The purpose of this study was to describe virtualization learning to write fairy tales based on anyflip products through SPADA Merdeka Campus. The research method used is qualitative. Data collection techniques using observation and interviews. Interviews were conducted with three people: one lecturer in the Appreciation of Indonesian Literature course, one student in the Appreciation of Indonesian Literature course, and one media colleague. The results of the study explain that learning to write fairy tales is carried out boldly. The platform chosen was SPADA Kampus Merdeka. There are several stages that must be passed in learning to write, including the pre-writing stage, the writing stage, and the post-writing stage. The product of this lecture is an anyflip based fable collection book.